Development of Turnreative Media to Improve Understanding of Derivatives in Mathematics Learning - Gelcy Vania Auliani; Merlisa; Rizma Nurfajriah Qolbi; Zulhilmi Gibran Pramudhia; Elsa Susanti; Zulkardi; Budi Mulyono; Meryansumayeka (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2025)
This research develops a game-based interactive learning media called Turnreative, which is valid, effective, and practical for improving students’ understanding of algebraic function derivatives. The development follows the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection instruments include validation sheets, practicality sheets, pre-test and post-test questions, and interviews. The collected data were analyzed using descriptive quantitative and qualitative techniques to determine the validity, practicality, and effectiveness of the media. The subjects were three public high school students in Palembang. Validation results showed the media was very valid, with scores of 82.5% from media experts and 89.5% from material experts. In terms of practicality, teachers gave 93.52% and students 93.33%. A small-scale trial indicated a significant increase in student understanding, from an average pre-test score of 33.33 to 90 in the post-test. The results conclude that Turnreative is feasible to use as a learning medium for algebraic function derivatives and has proven to be effective and efficient in enhancing students’ mathematical problem-solving skills.